Putting the "new" into new trade theory: Paul Krugman's Nobel memorial prize in economics. - Neary, J (Blackwell Publishing, 2009)
This paper reviews the scientific contributions of Paul Krugman to the study of international trade, on the occasion of his receipt of the 2008 Nobel Memorial Prize in Economics. A simplified exposition is presented of some of his principal findings, including: the effects of trade on firm scale and product diversity in a general model of monopolistic competition; the integration of monopolistic competition with factor endowments theory; the implications of transport costs, including home-market effects and the possibility of agglomeration in models of economic geography; and the positive and normative consequences of oligopolistic trade.